Multisensor Systems for Analysis of Liquids and Gases: Trends and Developments - Larisa Lvova (Frontiers Research Topics, 2019)
Nowadays the application of multisensor systems for the analysis of liquids and gases is becoming more and more popular in analytical chemistry. Such systems, also known as “electronic tongues” and “electronic noses” are based on various types of chemical sensors and biosensors with different transduction principles combined with multivariate data processing protocols. These instruments received significant interest due to their simplicity, low costs and the possibility to obtain reliable chemical information from complex unresolved analytical signals. A distinct feature of electronic tongues and noses is that they can be calibrated for prediction of complex integral features in samples, like e.g. taste, odor, toxicity, geographical origin, general conformity with certain standards, etc. – the tasks that otherwise would require involvement of complex analytical instrumentation, human or animal sensory panels. In the present eBook the original research and review articles in the area of multisensor approach are collected. They dedicated to the novel sensor materials development, measuring techniques evaluation, electronics, data processing protocols and practical applications. An editorial foreword article is followed by the researches authored by leading scientists in the field of chemical sensors and artificial sensing systems. With this eBook we hope to inspire further interest and new research efforts in this exciting area.